Evaluation Of Quality Management System Of ISO 9001:2008 In Vocational High Schools - Hendrina Widiastuty; Sutarto Sutarto; Haryo Aji Pambudi (Jurnal Penjaminan Mutu, 2019)
This research aims at evaluating the implementation of Quality Management System (QMS) of ISO 9001: 2008 in State Vocational High School 1 Surakarta and State Vocational High School 6 Surakarta through the Kirkpatrick model. The sample selection used the purposive sampling method with 77 teachers/staffs from the two schools. The data were collected with questionnaires and documentation. The implementation of QMS of ISO 9001: 2008 in both schools based on the input variables can be categorized as "very good with the score of 95 points out of 100 points. The results of the 3-behavior level evaluation on the QMS of ISO 9001: 2008 Implementation showed that the area of a) HR; b) the infrastructure; and c) the education process control and services in the State Vocational High School 1 and 6 Surakarta fell in the category of "mostly achieved". The results of a level 4 evaluation indicated the result of the graduates’ quality in both schools can be categorized as good with the mean of 58.33. The QMS of ISO 9001: 2008 implementation proved to have a good effect on the school administration system in both schools where the granting of QMS of ISO 9001: 2008 certificates in line with the achievement of “A” school accreditation over the past 10 years.